The Lindsey Stirling Effect - Grimshaw, Jeremy (Dialogue, 2015)
The article focuses on the cultural content of Mormonism's supposedly best-known/least-known musical protagonist, Lindsey Stirling. Topics discussed include the association among Mormon celebrity, Mormon normalcy and the dress worn by dancing violinist and YouTube star Lindsey Stirling to the Billboard Music Awards show, where she was to receive the Top Dance/Electronic Album honor, Stirling's story as an artistic development breakthrough, and where Stirling's audience appeal came from.